Epigenome-Wide Scan Identifies a Treatment-Responsive Pattern of Altered DNA Methylation Among Cytoskeletal Remodeling Genes in Monocytes and CD4+T Cells From Patients With Behcet's Disease - ALİBAZ ÖNER, FATMA; DİRESKENELİ, RAFİ HANER (WILEY, 2014)
Objective. The pathogenesis of Behcet's disease (BD), an inflammatory disease with multisystem involvement, remains poorly understood. This study was undertaken to investigate whether there are DNA methylation abnormalities in BD that might contribute to the pathogenesis of the disease. Methods. We examined genome-wide DNA methylation patterns in monocytes and CD4+ T cells from 16 male patients with untreated BD and age, sex, and ethnicity-matched healthy controls. Additional samples were collected from 12 of the same BD patients after treatment and achievement of disease remission. Genome-wide DNA methylation patterns were assessed using the Infinium Human Methylation 450 BeadChip array, which includes >485,000 individual methylation sites across the genome. Results. We identified 383 CpG sites in monocytes, and 125 in CD4+ T cells, that were differentially methylated between BD patients and controls. Bioinformatic analysis revealed a pattern of aberrant DNA methylation among genes that regulate cytoskeletal dynamics, suggesting that aberrant DNA methylation of multiple classes of structural and regulatory proteins of the cytoskeleton might contribute to the pathogenesis of BD. Further, treatment of BD modified the differences in DNA methylation observed in patients compared to controls; indeed, among CpG sites that were differentially methylated after disease remission versus before treatment, there was widespread reversal of the direction of aberrant DNA methylation observed between the patient and control groups. Conclusion. The results of this epigenome-wide study-the first such study in BD-provide strong evidence that epigenetic modification of cytoskeletal dynamics underlies the pathogenesis of BD and its response to treatment.
Keywords: T-CELLS; IMMUNE-COMPLEXES; MIGRATION; ORGANIZATION; EXPRESSION; SUGGESTS; GTPASES; IRTKS; RAC; RHO